Answer:
One of the negatives must go
Step-by-step explanation:
Answer:
n=2
2(n+8)=20
2n+16=20
-16 -16
<u>2n=4</u>
2 2
n= 2
There u go love
Step-by-step explanation:
<u>Answer:</u>
The Kinetic energy of the 110 kg linebacker is 1375 J
<u>Solution:</u>
The kinetic energy of an object is the energy produced by its velocity. Kinetic energy of an object is directly proportional to the mass and the square of the its velocity.
Therefore, the formula for kinetic energy is
![KE=\frac{1}{2} \times m v^{2}](https://tex.z-dn.net/?f=KE%3D%5Cfrac%7B1%7D%7B2%7D%20%5Ctimes%20m%20v%5E%7B2%7D)
Here, The linebacker’s mass m = 110 kg
The linebacker’s velocity v = 5 m/s
So by substituting the values,
The kinetic energy of linebacker is
![K E=\left(\frac{1}{2} \times 110 \times 5 \times 5\right) \text { Joules } \\\\ \Rightarrow (\frac{2750}{2}) Joules = 1375 Joules](https://tex.z-dn.net/?f=K%20E%3D%5Cleft%28%5Cfrac%7B1%7D%7B2%7D%20%5Ctimes%20110%20%5Ctimes%205%20%5Ctimes%205%5Cright%29%20%5Ctext%20%7B%20Joules%20%7D%20%5C%5C%5C%5C%20%5CRightarrow%20%28%5Cfrac%7B2750%7D%7B2%7D%29%20Joules%20%3D%201375%20Joules)
Answer:
The absolute value graph below does not flip.
Step-by-step explanation:
New graphs are made when transformed from their parents graphs. The parent graph for an absolute value graph is f(x) = |x|.
The equation used for a new graph transformed from the parent graph is in the form f(x) = a |k(x - d)| + c.
"a" shows vertical stretch (a>1) or vertical compression (0<a<1), and <u>flip across the x-axis if "a" is negative</u>.
"k" shows horizontal stretch (0<k<1) or horizontal compression (k>1), and <u>flip across the y-axis if "k" is negative</u>.
"d" shows horizontal shifts left (positive number) or right (negative number).
"c" shows vertical shifts up (positive) or down (negative).
The function f(x)=2|x-9|+3 has these transformations from the parent graph:
a = 2; Vertical stretch by a factor of 2
k = 1; No change
d = 9; Horizontal shift right 9 units
c = 3; Vertical shift up 3 units
Since neither "a" nor "k" was negative, there were no flips, <u>also known as reflections</u>.
Answer:
Step-by-step explanation:
x = 1 - i sqrt(2) ^ y = 10 + i sqrt(2)
x = 1 + i sqrt(2) ^ y = 10 - i sqrt(2)